Model Petri Net Produksi Tahu Pada Industri Skala Rumah Tangga - Deny Murdianto; Shinta Tri Kismanti; Dwi Santoso (Universitas Airlangga, 2023)
The process of making tofu includes several steps, namely the process of soaking soybeans, washing soybeans, milling soybeans, boiling or cooking, filtering, settling and adding vinegar. The purpose of this study it was to obtain a Petri Net model of the tofu making process and perform simulations with signed Petri Nets. Simulations are carried out to determine the dynamics that occur during the process of making tofu. The data used is by observation in a household-scale tofu and tempeh processing industry in Tarakan City. The Petri Net model obtained consists of six transitions and ten places. Assuming that every enable transition will always be fired in every state, there are sixteen possible states that can be achieved in the Petri Net simulation.